Indonesia’s Self Identity in the Development Assistance Policy through South South and Triangular Cooperation (SSTC) - Lucke Haryo Saptoaji Prabowo (Institute of International Studies, 2020)
This article aims to examine the link between self-identity and foreign policy, particularly focusing on how state’s self-identity is built and sustained through policy. Using Indonesian development assistance policy through South South and Triangular Cooperation (SSTC) as a case study, this article finds that Indonesia self-identifies as a middle power country with strong affiliation towards developing countries as a result of national role conception processes. This self-identity in turn are built and sustained through SSTC development assistance policy, due to the suitability of role obligations as a middle power country with the values carried by the act of providing development assistance, as well as the deeply rooted historical dynamics of SSTC development policy with developing country status.